Analisis Kelembagaan dan Kerangka Regulatif Pemerintah Daerah dalam Literasi Media Keluarga - Syarafina Dyah Amalia; Dwiki Oktobrian; Asti Inayah; Tenang Haryanto (Fakultas Hukum Universitas Bangka Belitung, 2026)
This study analyses local government institutions and regulatory frameworks in mainstreaming family media literacy in Indonesia. Digital transformation poses challenges for families, including exposure to misinformation, harmful content, and weak information verification skills. Local governments are in a strategic position through their authority over education, public communication, child protection, and community literacy. However, the results of the study show that there is no clear institutional structure and no regional regulations that explicitly regulate family media literacy. This study uses a normative-juridical method through a statute and conceptual approach to map legal gaps, overlapping authorities, and inconsistencies between national and regional regulations. The main findings indicate institutional fragmentation, institutional void, and obscurity of norms as obstacles to the implementation of family media literacy. A comparison with international standards (UNESCO MIL, UK Online Media Literacy Strategy, and Japan's Family ICT Framework) shows that Indonesia lags behind in providing a local regulatory architecture. This study offers an ideal regulatory model based on four pillars: regulation, inter-agency coordination, programme standardisation, and family-based indicator evaluation. The results of this study contribute theoretically to strengthening the study of local government law and practically to the drafting of a Regional Regulation on Family Media Literacy.